Heterogeneous Catalysis of Multiple-Electron-Transfer Reactions at Nanoparticle-Modified Electrodes - Laborda, E; Neumann, C; Wang, Y; Ward, K; Molina, A; Compton, R (2014)
In some important electrochemical systems, the degree of electro-reduction (or electro-oxidation) of the reactant at the electrode surface depends on the extent of a surface-catalysed reaction that involves intermediates formed by electron transfer. The catalytic properties of the electrode surface towards this heterogeneous reaction, therefore, can control the final product of important processes, such as the electro-reduction of oxygen and some organic compounds. The modelling of the ECₕₑₜEfd mechanism (where Chet is a heterogeneous chemical reaction and Efd indicates that the second electron transfer is fully driven) is considered in this paper at nanoparticle-modified electrodes and homogeneous surface macroelectrodes. The influences of the chemical and electrochemical kinetics as well as the characteristics of the mass transport are investigated. The results enable us to propose procedures for the identification and characterisation of the surface-catalysed process and for the optimisation of electrode modifications.